EMPOWERMENT OF COASTAL COMMUNITIES IN ALLENGING POVERTY IN INDONESIA - Yanuardin Yanuardin (Proceeding International Seminar of Islamic Studies, 2022)
Marine products are the main source of livelihood for coastal communities who live from marine products or it can even be said that the economic base of coastal communities is the fishery sector. The high element of uncertainty in fishing, especially for coastal communities, has become a growing general perception regarding the needs of fishermen's families and generally coastal communities. The history of poverty in families who depend on what the sea provides them often becomes an illustration of the pressure situation in this sector. Currently, there are still many fishermen living below the poverty line. We are trying with regulations regarding fishermen, we hope to improve welfare even better than before. This study aims to examine how the empowerment of coastal communities in an effort to alleviate poverty in Indonesia. The results of the research show that first the government needs to build solidarity and collective action in the community. Second, there is a need for a new technology approach that is more successful and efficient to the community and third, that it brings people closer to the market.Keywords:Empowerment, Coastal Communities, Poverty